Peran Humas Di Instansi Pemerintahan Kota Salatiga Dalam Penyebarluasan Informasi Program Kerja Pemerintah Stunting Melalui Media Sosial - Manuhara, Febryana Kayla; Kristiyani, Dian Novita (IAINU Kebumen, 2024)
Salatiga, a small city in Central Java Province with a population of 192,322 in 2020, faces significant social, economic, and health challenges due to overcrowding, namely stunting. This study examines the role of public relations in Salatiga city government in disseminating information related to the “Convergence Action” program, a government initiative aimed at reducing stunting, a health problem exacerbated by high population density. This study used a descriptive qualitative approach, with data collection techniques in the form of interviews, observation, and documentation. The results showed that the public relations of Salatiga City Government has an important role in fostering relationships, supporting management, and building the city's corporate image through social media. However, there are barriers to coordination, such as delays in disseminating materials for publication, which reduce active community participation and potentially slow down the reduction of the number of stunting. These barriers reduce the effectiveness of the stunting program's information dissemination and may interfere with achieving the program's objectives, highlighting the need for better communication strategies to increase community engagement and program success.